Performance Appraisal and Innovative Behavior in the Digital Era - Curzi, Ylenia; Fabbri, Tommaso; Scapolan, Anna Chiara; Boscolo, Stefano (Frontiers in Psychology, 2019)
In digital competitive environments, organizations’ ability to innovate is more than ever the key to competitive advantage. One way to cope with this increased pressure for innovation is to capitalize on employees’ ability to generate new ideas and use these as building blocks for new and better products, services, and work processes. Individual innovation thus emerges as a key competence required from workers, in turn crucially affecting the way managers make employees contribute to organizational goals and assess their performance. This study draws on the process-based approach to HRM (Bowen and Ostroff, 2004) suggesting that HRM practices may have a signaling effect, to address the following research question: which specific characteristics of performance appraisal are more likely to be perceived as promoting individual innovation at work? To address this issue, we carried out a survey on 865 employees working in large, multinational firms operating in digitalized sectors or industries with the potential to become digitalized. We collected data on the main characteristics of the performance appraisal systems adopted by the firm where respondents work, as perceived by employees themselves. We gathered also data on the respondents’ overall perception that performance appraisal boosts innovative work behavior. Then, we employed logit analysis to test the relationship between data on performance appraisal systems and data on effectiveness of performance appraisal as a booster of innovative work behavior. Our results reveal that, as compared to informal feedback, formal performance appraisal is more likely to reduce the perception that performance appraisal promotes individual innovation and creativity at work. In addition, we found that in the employees’ perception performance appraisal focused on the achievement of pre-set, quantitative outcomes is more likely to affect positively innovative work behavior than appraisal focused on pre-defined skills that employees exhibited performing their work. However, performance assessment focused on new competences developed by the employees has a perceived positive impact even stronger than result-oriented appraisal. Taken together, these results contribute to advance our understanding of how organizations should evaluate employees in the digitalization era.